The Hyphosphere of Leaf-Cutting Ant Cultivars Is Enriched with Helper Bacteria - Martiarena, Maria Jesus Sutta [UNESP]; Deveau, Aurelie; Montoya, Quimi Vidaurre [UNESP]; Flórez, Laura V.; Rodrigues, Andre [UNESP] (Springer Nature, 2023)
Bacteria can live in a variety of interkingdom communities playing key ecological roles. The microbiome of leaf-cutting attine ant colonies are a remarkable example of such communities, as they support ants’ metabolic processes and the maintenance of ant-fungus gardens. Studies on this topic have explored the bacterial community of the whole fungus garden, without discerning bacterial groups associated with the nutrient storage structures (gongylidia) of ant fungal cultivars. Here we studied bacteria isolated from the surface of gongylidia in the cultivars of Atta sexdens and Acromyrmex coronatus, to assess whether the bacterial community influences the biology of the fungus. A total of 10 bacterial strains were isolated from gongylidia (Bacillus sp., Lysinibacillus sp., Niallia sp., Staphylococcus sp., Paenibacillus sp., Pantoea sp., Staphylococcus sp., and one Actinobacteria). Some bacterial isolates increased gongylidia production and fungal biomass while others had inhibitory effects. Eight bacterial strains were confirmed to form biofilm-like structures on the fungal cultivar hyphae. They also showed auxiliary metabolic functions useful for the development of the fungal garden such as phosphate solubilization, siderophore production, cellulose and chitin degradation, and antifungal activity against antagonists of the fungal cultivar. Bacteria-bacteria interaction assays revealed heterogeneous behaviors including synergism and competition, which might contribute to regulate the community structure inside the garden. Our results suggest that bacteria and the ant fungal cultivar interact directly, across a continuum of positive and negative interactions within the community. These complex relationships could ultimately contribute to the stability of the ant-fungus mutualism.
Keywords: Attine ants; Bacteria-fungus interaction; Biofilm; Helper bacteria